Strategi Komunikasi Pemasaran Taxi Ngurah Rai Bali dalam Mengatasi Persaingan Bisnis di Era Digital - Dewi, Dewa Ayu Anggi Diantari; Ramadiansyah, Sahri Aflah (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the marketing strategy implemented by the Ngurah Rai Taxi Transportation Cooperative in responding to competition in the transportation industry in the digital era. Unlike application-based transportation companies, Ngurah Rai Taxi is a local transportation service provider that does not use a booking application, but instead relies on direct marketing activities at Ngurah Rai International Airport and the use of social media as a marketing communication tool. This study employs a descriptive qualitative approach, with data collected through in-depth interviews, field observations, and documentation. The research informants consist of an operational manager, field staff, a social media administrator, and taxi drivers. The findings indicate that the marketing strategy of Ngurah Rai Taxi emphasizes personal interaction, trust, and its image as an official airport taxi. Analysis using the AIDA model shows that consumer attention and interest are built through physical presence in the airport arrival area and direct communication, while desire and action are influenced by factors such as safety, fare certainty, and service comfort. This study confirms that direct service-based marketing strategies remain relevant and competitive within the context of Bali’s tourism market.